Penerapan Etika Bisnis Islam Dalam Meningkatkan Usaha Mikro Kecil dan Menengah (UMKM) - Lubis, Melati Br.; Siregar, Nur Khofifah; Maulida, Sifa; Marpaung, Wardatun Thaibah; Marpaung, Syafri Fadillah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Micro, Small, and Medium Enterprises (UMKM) serve as the backbone of Indonesia's economy. However, these enterprises often encounter various challenges in running their businesses, one of which is intense competition. The application of Islamic business ethics can serve as a solution to address these challenges. Islamic business ethics comprises a set of principles and values that regulate business behavior in accordance with Islamic teachings. It emphasizes the importance of justice, honesty, and social responsibility.This research aims to examine the impact of implementing Islamic business ethics on the enhancement of UMKM. The study employs a literature review method, gathering data from various journals and articles. The research findings indicate that the application of Islamic business ethics has a positive influence on the improvement of UMKM.